Perioperative Deep Vein Thrombosis Risk Stratification: A Comparative Analysis of Free and Pedicled Flap Patients. (3rd October 2016) - Sinha, Sumi; Puram, Sidharth V.; Sethi, Rosh K. V.; Goyal, Neerav; Emerick, Kevin S.; Lin, Derrick; Durand, Marlene L.; Deschler, Daniel G.
Abstract : Patients with head and neck cancer who undergo reconstructive surgery are at risk for deep venous thrombosis (DVT), but the risk profile for patients undergoing major flap reconstruction is highly variable. Herein, we report our findings from a retrospective analysis of head and neck cancer patients (n = 517) who underwent free (n = 384) or pedicled (n = 133) flap reconstructive operations at a major tertiary care center from 2011 to 2014. DVTs developed perioperatively in 9 (1.7%) patients. Compared with pedicled flap patients, free flap patients had a longer mean operative time (421.4 ± 4.4 vs 332.7 ± 10.7 min, P <. 0001), but the DVT incidence did not differ significantly between free and pedicled flap patients (1.6% vs 2.2%, respectively, P =. 28). These data suggest that perioperative DVT risk in head and neck oncology patients may be largely similar regardless of the reconstructive strategy pursued.